Abrasion resistance of concrete made with micro fibers and recycled granulated rubber - Nenad Ristić; Ćurčić Gordana Topličić; Dušan Grdić (Zaštita Materijala)
Durability of concrete engineering structures in most part depends on the resistance of their surface to mechanical abrasion. The paper presents the results of experimental test of performance of concretes made with micro fibers and recycled granulated rubber in fresh and hardened state, as well as the comparative analysis of wear grinding resistance and hydroabrasive resistance of concrete. Six batches of concrete were made for the tests: reference concrete, concrete with partial replacement of fine river aggregate with recycled granulated rubber, two batches with the addition of polypropylene fibers (monofilament and fibrillated) and two batches of concrete with addition of steel hook ended fibers (short - having length 30 mm and long - having length 50 mm). It was found that the addition of micro-reinforcement or recycled rubber contributes to the increase of concrete wear grinding resistance and hydro-abrasive resistance. There is a difference in the abrasive resistance depending on test method.